(untitled) (BIRDEM Medical Journal, 2022)
Background: Hydronephrosis (HDN) due to pelviureteric junction (PUJ) obstruction is a common congenital anomaly of urinary tract which is generally treated by pyeloplasty. But the extent of functional recovery is still debated. Considering the existing controversies, this study was designed to evaluate the changes of renal function after pyeloplasty measured by 99mTc-DTPA renography. Methods: This study was done in the department of urology, National Institute of Kidney Diseases and Urology (NIKDU) and Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital from July 2014 to December 2020. Sixty patients were included in this study and underwent Anderson-Hynes (A-H) dismembered pyeloplasty for PUJ obstruction. All patients were evaluated with diuretic 99mTc-DTPA renogoam before and at 3 and 6 months after pyeloplasty. Improvement of renal function was evaluated by comparing preoperative and postoperative differential renal function (DRF) and glomerular filtration rate (GFR). Results: Sixty patients (34 male and 26 female) with unilateral HDN due to PUJ obstruction were included in this study with mean age of 15.6 years (ranged from 3 – 38 years). Out of 60 patients, 56.7% had left sided HDN and 43.3% had right sided HDN. The mean preoperative DRF was 16.72 ± 8.35% at baseline which increased to 26.03 ± 7.08% at the end of 3rd month and 28.15 ± 5.84% at the end of 6th month. The mean preoperative GFR was 14.29 ± 6.73 ml/min/1.73 m2 at baseline which increased to 24.13 ± 5.31ml/min/1.73 m2 at the end of 3rd month and 27.38 ± 4.78 ml/min/1.73 m2 at the end of 6th month. Conclusion: The result demonstrates that, after pyeloplasty renal function improves. Highest recovery of renal function noted in patients with poor pre-operative DRF and GFR. BIRDEM Med J 2022; 12(2): 142-146